2017
DOI: 10.1103/physrevphyseducres.13.020128
|View full text |Cite
|
Sign up to set email alerts
|

Investigating undergraduate students’ ideas about the fate of the Universe

Abstract: As astronomers further develop an understanding of the fate of the Universe, it is essential to study students' ideas on the fate of the Universe so that instructors can communicate the field's current status more effectively. In this study, we examine undergraduate students' preinstruction ideas of the fate of the Universe in ten semester-long introductory astronomy course sections (ASTRO 101) at three institutions. We also examine students' postinstruction ideas about the fate of the Universe in ASTRO 101 ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Moreover, the nature of many astronomical phenomena seems to be counterintuitive or even contradictory to our previous knowledge of the world (Kersting et al, 2018). Besides, topics of astronomy challenge us because of the vast scale of the Universe and its multidimensionality (Bakas & Mikropoulos, 2003;Conlon et al, 2018;Eriksson et al, 2014;Kersting, 2020).…”
Section: Astronomy Education and The Virtual Universementioning
confidence: 97%
“…Moreover, the nature of many astronomical phenomena seems to be counterintuitive or even contradictory to our previous knowledge of the world (Kersting et al, 2018). Besides, topics of astronomy challenge us because of the vast scale of the Universe and its multidimensionality (Bakas & Mikropoulos, 2003;Conlon et al, 2018;Eriksson et al, 2014;Kersting, 2020).…”
Section: Astronomy Education and The Virtual Universementioning
confidence: 97%
“…Science education research has repeatedly found that secondary school students are motivated by topics of astrophysics and astronomy (Angell et al, 2004;Conlon et al, 2018;Eriksson et al, 2014;. It is thus not surprising to see that ReleQuant students felt motivated and engaged to learn about Einstein's theory of gravity, space, and time.…”
Section: Student Motivationmentioning
confidence: 99%
“…activity's focus on an understanding of cosmology adds to an area of education that is often missing in the average science classroom, 9,10 supplementing other works focused on replicating astronomical experiments, like determining the Hubble constant. 11,12 Additionally, once students have completed the activity, they have performed a part of a Nobel Prize-winning analysis, showing them that they can participate in important science, whatever their educational background.…”
Section: Astronotesmentioning
confidence: 99%